The place and the value of phylogeny in paleoanthropology: just talking or never mind? - Valéry Zeitoun (UISPP Journal)
The diffusion of sensational and incomplete analyses, as well as the misinterpretation of data, has led to a series of paleoanthropological paradigms which are, for the most part, purely speculative. These practices result from a lack of knowledge of the basic rules of classification, resulting in phylogenetic paleoanthropological discourses that are usually decoupled from the rules of systematics. Since the 1960s paleoanthropological research has focused on the nomenclature and taxonomy of the Hominidae, reporting on the work of Dobzhansky and Mayr. Today, the paleoanthropological discourse incorporates phylogenetic ideas but paleoanthropologists neither use the tools nor the methods of phylogeny, or the rules of systematics. This issue was described by Bonde at a time when the cladist school was beginning to influence some paleoanthropologists. In subsequent years, discussions on the value and polarity of observed characteristics arose, replacing earlier debates based on overall similarity. Authors proposed species lists based on the presence of autapomorphic characters, and finally, cladograms were produced. However, after two decades, discussions on the constitution of OTU (Operational Taxonomic Unit), the definition of characteristics, variability, and over-representation or redundancy of certain characteristics led to the rejection of cladistics in paleoanthropology. Despite the fact that Barriel and Tassy responded to these objections in the 1990s, their points were ignored or misunderstood by paleoanthropologists and, in the 2000s, cladistics was almost completely abandoned in favor of a return to classical evolutionary systematics or the new craze for phenetics; two quantitative approaches. This paper investigates Niels Bonde's long-standing question and concludes that this question is still relevant today: 'Is it really impossible to transmit such a simple and logical method (phylogenetic systematics) to anthropologists or do they not care about it?'